Faktor yang Memengaruhi Keluarga Berencana (KB) Pria dengan Paritisipasi Pria dalam Keluarga Berencana di Wilayah Kerja Puskesmas Sedayu II - Susi Ernawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
The enrollment man in the use of contraceptives in indonesia is still very low only 2.1% kb participants men and they generally wearing a condom .This percentage lower if than in other countries, like Iran 12%, Tunisia 16%, Malaysia 9-11%.Of the total number of acceptors in Indonesia about 97% are women. The purpose of this research is to know what factors affecting family planning (KB) man with paritisipasi man in family planning in the work area of Puskesmas Sedayu II. Population in research it is a whole fertile couples active attending the program at Puskesmas Sedayu II. A population of as many as 170 persons, the sample of the 63. Analysis the data used was analysis bivariat and multivariate. The results of the study participation man not directly to the days of 20 to 30 years as many as 100%, participation man not directly with junior as many as 93.3%, participation pre indirect the number of children <2 as many as 100%, participation man not directly with income ≥rp. 1.168.300 as many as 100%, participation man not directly with knowledge enough as many as 100%, participation man not directly with social and cultural back 100%. Multivariate test results obtained not a significant relation exists between the ages of, education, the number of children, income, knowledge, social and cultural by participation man in family planning.